The Effect of Learning Interest on Students' Concept Understanding Ability Against Subject Pressure - Pramita, Cici; Tasa Ratna Putri (Yayasan Nurul Yakin Bunga Tanjung, 2023)
This article discusses the effect of interest in learning on students' ability to understand physics concepts at SMA N 06 Sarolangun on the subject of pressure. This study uses a quantitative approach with correlational methods. The population of this study were students in classes XI IPA 1, XI IPA 2, and XI IPA 3. The sampling was carried out using a purposive sampling technique, namely class XI IPA 1. The data collection technique in this study was by using tests and non-tests. The test used is in the form of post-test questions with a total of 5 multiple-choice questions to measure students' understanding of concepts, especially on the subject of pressure. Meanwhile, non-test data collection is in the form of a questionnaire to measure how interested students are in learning. The questionnaire used totalled 10 question items. To find out if students were interested, students had to answer 9 out of 10 questions in a positive direction, with the answer choices being interested up or interested and very interested. And for understanding the concept, If students can answer four questions, then they are started to understand. But conversely, if they answer the 3 questions below, then they are stated not to understand the understanding of the concept of physics regarding pressure material. In accordance with the results of the study using data that had been processed using proven quantitative methods and it was found that the learning interest of class XI IPA students was very low and affected how students' conceptual understanding of physics, especially the subject of pressure